Proposed collection development policy statement for Claret School of Quezon City High School Library - Pujol, Yulysses V.; Arellano, Clarita A. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The Claret School of Quezon city High School Library is an independent and non-profit institution modeled to support the information needs of the students, faculty members and personnel of the Claret School of Quezon City High School. It is therefore understood that the main responsibility of the head librarian is to provide information that will support the curriculum and as well as personal needs. But before the librarian do all these tasks, it is necessary for him/her to be guided by some policies to ensure that he/she is getting the right materials. In order to identify what kind of materials should be included in the collection a set of rules or guidelines for the development of the library's resources must be created.
In order to formulate a good Collection Development Policy for Claret School of Quezon City High School Library, the researcher conducted the following methods: 1) Document Analysis, 2) Use Pattern Analysis, 3) Assessment of the Library's Collection, and 4) Selection, Acquisition Practices Analysis. Findings show: a. The collection is sufficient to meet the personal needs and demands of the library's clienteles. b. The collection is not sufficient to support the Basic Education Curriculum requirements of the Department of Education. c. The collection is not sufficient to support the school's mission statement. d. There are no written guidelines that will help in the selection and acquisition procedures.
The study therefore concluded that strengthening the above mentioned weaknesses of the library should be the main focus of the Collection Development Policy of the Claret School of Quezon City High School Library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Claret School of Quezon City High School Library; Collection development (Libraries) -- Policy statements; School libraries -- Collection development -- Philippines -- Quezon City